Effects of Different Protein Sources on Amino Acid Absorption and Plasma Appearance of Tryptophan, Large Neutral Amino Acids, and Tryptophan Metabolites in Pigs - Giezenaar C; Montoya CA; Kreutz K; Hodgkinson S; Roy NC; Mace LJ; Fraser K; Fernstrom JD; McNabb WC; Moughan PJ (Elsevier Inc on behalf of American Society for Nutrition, 2024)
BACKGROUND: Absorption of tryptophan (TRP) across the gut epithelium is potentially modulated by competing large neutral amino acids (LNAAs), which could affect the appearance of TRP and its metabolites in the bloodstream. OBJECTIVES: This study aimed to determine, in a growing pig model of an adult human, the absorption of TRP and other LNAAs from the gastrointestinal tract, and plasma appearance of TRP, LNAAs, and TRP metabolites, in response to dietary proteins varying in TRP content. METHODS: Pigs were adapted for 7 d to each of 4 diets that differed in their protein source and TRP content: 1) alpha-lactalbumin (AL; 9.95 mg TRP/g diet DM), 2) whey protein (6.59 mg TRP/g), 3) casein (3.73 mg TRP/g), or 4) zein (0.14 mg TRP/g). On day 8, pigs were euthanised after a 12-h fast (baseline), or 1, 2, 3, 4, or 6 h after they received a test meal consisting of 45 g protein, or a protein-free meal (n = 6 pigs at each time in each meal group). Tryptophan and LNAA absorption from the small intestine, and appearance of TRP, LNAAs, and TRP metabolites (melatonin, serotonin, kynurenine pathway metabolites), in the portal vein and systemic circulation, were determined. RESULTS: AL intake resulted in sustained elevated plasma TRP concentrations after an overnight fast. The amount of TRP absorbed was dose-dependently related to protein TRP content (P = 0.028), with fastest rates for pigs fed AL (371 mg/h). Portal and systemic plasma TRP, TRP/LNAA, and the TRP metabolites were highest (P ≤ 0.05) after AL intake, and remained above baseline levels for ∼4 h postprandially. Absorption rates of TRP correlated with postprandial plasma TRP and TRP metabolites (P ≤ 0.05). CONCLUSIONS: In adult humans, postprandial plasma TRP and TRP metabolite concentrations can likely be modulated by the TRP content of the meal.
Keywords: absorption; dietary protein; metabolites; pigs; tryptophan